Non-Invasive Prenatal Testing with Next Generation Sequencing Methods in Birth Defect Pregnancy: A Pilot Study - Anom Suardika; Anak Agung Ngurah Jaya Kusuma; Ni Gusti Ayu Manik Ermayanti; Endang Sri Widiyanti; I Gusti Ngurah Agung Satria Wibawa; Divika Silvana; Anak Agung Gede Raka Budayasa; Ni Nyoman Ayu Dewi; I Made Jawi; H. Sunny Sun; Yen-An Tang (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Identification of cell-free foetal DNA (cffDNA) in maternal blood, combined with next-generation sequencing (NGS) advancement, has paved the way for non-invasive prenatal screening to detect foetal aneuploidies. However, there is limited evidence on its diagnostic accuracy when compared with gold-standard invasive tests specifically in pregnancies complicated by birth defects in Indonesia. This study was conducted to evaluate the precision of non-invasive prenatal testing (NIPT) using NGS and ultrasound findings compared with the established benchmarks of amniocentesis and neonatal karyotyping through G-banding analysis, which is an invasive procedures, in a private laboratory setting for pregnancies with birth defect.METHODS: An observational cohort study involving pregnant women with foetal birth defects in central nervous system, facial, heart, gastrointestinal tract, urinary tract abnormalities and suspected Down Syndrome was conducted. The foetal birth defects were identified in the first trimester with ultrasound screening. Venous blood was drawn from the mother for NGS-based NIPT examination. As a gold standard, amniocentesis or neonatal G-banding karyotyping was conducted.RESULTS: Using G-banding karyotyping as gold standard, the results indicated that NIPT using the NGS method and ultrasound findings achieved 100% sensitivity, 100% specificity, and 100% accuracy in detecting trisomy 13, 18, and 21, as well as foetal sex chromosome abnormalities. Additionally, a case of tetrasomy 9p was identified through G-banding karyotyping, which was associated with multiple clinical abnormalities.CONCLUSION: NIPT with NGS methods and ultrasound findings demonstrated 100% accuracy for the screening of trisomy 13, 18, and 21 in birth defect pregnancy, which is comparable with G-banding analysis as a gold standard. Therefore, this suggest that these approaches offer a safe early detection, highly accurate alternative in high risk setting, compared to invasive procedure in Indonesia where access to such testing may be limited. KEYWORDS: G-banding karyotyping, next generation sequencing, non-invasive prenatal testing